FVIII/PC and ADAMTS13/VWF ratio to predict liver-related events and mortality in patients with ACLD. (March 2023) - Giuli, L.; Pallozzi, M.; Santopaolo, F.; Gasbarrini, A.; De Cristofaro, R.; Pompili, M.; Ponziani, F.R.
Abstract : Introduction: Recent studies analyzed the prognostic role of coagulation parameters such as factor VIII (FVIII) /protein C (PC) ratio on advanced chronic liver disease (ACLD) decompensation or liver-related outcomes [1]. We recently demonstrated that a disintegrin and metalloprotease with thrombospondin 1 repeats number 13 (ADAMTS-13)/von Willebrand factor (VWF) ratio is useful to predict the development of portal vein thrombosis (PVT) [2], but little is known about its role as marker of decompensated ACLD (dACLD). Aim: To investigate the prognostic role of ADAMTS13/VWF ratio on the development of dACLD and compare it with FIII/VWF ratio. Materials and Methods Results: We assessed 86 patients with ACLD (median age 66 years; 65.47% male; etiology viral/nonviral 50%/50%; Child Pugh A/B/C 80.2%/15.1%/4.7% and median model for end-stage liver disease [MELD] 8). 20 patients (23.25%) developed decompensated ACLD after a median of 48.8 months and presented a significantly a lower ADAMTS-13/VWF ratio and a higher FVIII/PC ratio compared to their counterparts maintaining compensated ACLD (ADAMTS-13/VWF 0.26 [0.22-0.41] vs 0.52 [0.16-0.62], p<0.0001; FVIII/PC 2.62 [1.87-3.81] vs 1.44 [1.13-1.77], p<0.0001 Figure 1A-B). Both these indices correlated with Child Pugh and MELD score, although FVIII/PC ratio showed the strongest correlation with clinical and coagulation parameters (Figure 1C). Moreover, ADAMTS-13/VWF ratio or FVIII/PC ratio showed a good prognostic ability on dACLD-free survival and liver-related death (p<0.0001, Figure 1D-E), although ADAMTS-13/VWF ratio showed a limitation in identifying clinically relevant early events. Finally, the four patients who developed portal vein thrombosis (PVT) had a lower ADAMTS-13/VWF or a higher FVIII/PC compared to their counterparts. Conclusions: Coagulation parameters, historically used only for assessing bleeding risk in patients with ACLD, are instead harbingers of important prognostic information. Indeed, ADAMTS13/VWF ratio and FVIII/PC ratio correlate with liver disease severity and can predict liver-related death or decompensation in patients with ACLD.